Pedagogically Neglected Adolescents - Janulaitienė , Nijolė (Acta Paedagogica Vilnensia, 1991)
The article contradicts the opinion often voiced in the discussions of the teachers, that it is not worth wasting effort to work with hard-educated teenagers, and that policemen and not teachers should take care of the juvenile crime prevention. It is noted that today’s criminal youngsters, angry, aggressive or sluggish, who see no prospects in life, are yesterday’s pedagogically neglected teenagers, and neither the family nor the school should avoid its responsibility. In order to develop an effective methodology for overcoming pedagogical and social neglect, it is important to have knowledge of this phenomenon. The article presents empirical survey carried out on pedagogically neglected adolescents in Kaunas. The survey of 1988 was of a more declarative nature. The aim was to identify the external factors influencing pedagogical neglect. Another survey "Educational neglect and overcoming it through the cooperation of schools, families and society" was carried out in 1988-1989. This survey aimed to clarify the external factors and to identify internal causes leading to pedagogical neglect, and to prepare methods of coping with it.
Keywords: educational neglect; delinquent behaviour; socio-cultural environment; prevention